Flow boiling bubble dynamics in a graphene-coated minichannel - Kochkin Dmitry; Belosludtsev Valentin; Zaitsev Dmitry; Arkhipov Vyacheslav; Kabov Oleg (E3S Web of Conferences)
This paper is devoted to the study of the dynamics of vapor bubbles during water flow boiling in a graphene-coated minichannel. Graphene was synthesized directly on the surface of the boiling surface. It was found that applying a graphene film to a copper surface does not lead to a significant change in wettability with water. During the experiments, a significantly larger number of bubbles were observed on the graphene-coated surface than on the surface without graphene.